Typographic design form and communication - Carter, Rob; Meggs, Philip B.; Day, Ben. (Hoboken, N.J. John Wiley & Sons, 2012)
"Full-color throughout and be supported by a companion website and instructor ancillaries, Typographic Design has been a consistent knowledge source on the ins and outs of working with type. The new Fifth Edition is updated throughout, including many new images and case studies. It also contains new information on visual metaphor, analogy, metonymy, multi-modal typography, and new cultural developments in type. Other new additions include a chapter on typography on the screen, as well as up-to-date information on typographic technology"
Includes bibliographical references (p. 346-348) and index.
Keywords: Graphic design (Typography)